The Effect of Retail E-Commerce Sales and Domestic Direct Investment on the RCA Value of the Indonesian Medium High Technology Sector: RLS and FMOLS Approach - Wiryawan, Driya; Rodliyah, Nunung; Wahyudi, Heru; Leny, Sandra Mei (Journal of Ecohumanism, 2024)
Revealed Comparative Advantage (RCA) is a key indicator that reflects the competitiveness of a country and plays an important role in determining the position of a country in the global value chain, especially in the medium high technology sector. A high RCA value indicates a country's ability to compete effectively, while a low RCA value may indicate a greater dependence on imported products and a weakened position of local industries. Factors that influence the RCA value are Retail E-commerce Sales and Domestic Direct Investment. This study explores the interaction dynamics of Retail E-commerce Sales and Domestic Direct Investment in strengthening the comparative competitiveness of Indonesia's medium-high technology industry as part of a strategy to improve Indonesia's position in the global value chain. Robust Least Squares (RLS) and Fully Modified Ordinary Least Squares (FMOLS) methods are used to analyse data from 2017 to 2022, which shows that Retail E-commerce Sales has a significant negative influence on the RCA value of Indonesia's Medium High Technology sector caused by competitive pressure from imported products. On the other hand, Domestic Direct Investment has a significant positive impact on the RCA value by playing a role in increasing production capacity, technology transfer, and local innovation. This result confirms the importance of policies that support increased domestic investment while strengthening the competitiveness of domestic products amid the rapid growth of e-commerce. The findings of this study provide a strategic foundation for sustainable industrialisation policies and the development of Indonesia's Medium High Technology Sector competitiveness in the global market.